Implementation of Femovenart Mechanical Compression (Femopress) in Femoral Sheath Removal for Post-Cardiac Catheterization Patients - Bambang Julianto; Fery Agusman Motuho Mendrofa; Blacius Dedi (GLOBAL HEALTH SCIENCE GROUP, 2026)
Manual femoral sheath removal following percutaneous coronary intervention (PCI) remains a major challenge in interventional cardiac nursing practice. Variations in manual pressure, prolonged compression duration, and nurse fatigue can lead to inconsistent hemostasis and potential peripheral complications. To address these issues, an innovative mechanical compression device Femovenart Mechanical Compression (Femopress) was developed as a locally engineered nursing tool designed to provide consistent, ergonomic, and safe compression after cardiac catheterization. This action research study was conducted at the Cathlab Unit of Dr. Loekmono Hadi General Hospital, Kudus, Central Java, from May to June 2025. The study involved four Cathlab nurses as collaborative practitioners and twenty post-PCI patients with femoral access. Data were collected through direct observation, peripheral safety assessment using six indicators (pulse, skin color, oxygen saturation, hematoma, paresthesia, and pain), and focus group discussions (FGDs). Triangulation was performed with three experts: an academic supervisor, an interventional cardiologist, and a senior Cathlab nurse. Quantitative data were analyzed descriptively, while qualitative data were processed using thematic content analysis. Prior to the innovation, manual compression required 15–20 minutes and often caused nurse fatigue and inconsistent hemostasis. Implementation of Femopress reduced compression time to 13–18 minutes, maintained optimal hemostasis, and improved peripheral safety. Based on the Abukays Peripheral Safety Scale, 90% of patients achieved “safe” scores (9–12), with no secondary bleeding or hematoma. Six FGD themes emerged: (1) manual practice limitations, (2) unavailability of special tools, (3) inadequacy of facilities, (4) need for dedicated compression devices, (5) positive evaluation of Femopress, and (6) expectations for future development. The Femopress innovation effectively improves procedural efficiency, reduces nurse workload, and enhances patient comfort and safety in femoral sheath removal after PCI. This device demonstrates strong potential as a standard nursing technology for Cathlab practice and a model of nursing-led innovation in cardiovascular care.